Optimization of Ferrites Structure by Using a New Core-Less Design Algorithm for Electric Vehicle Wireless Power Transfer - Kaiwen Chen; Jianfei Pan; Yun Yang; Ka Wai Eric Cheng (Energies, 2021)
In order to improve the customers’ continuous usage of electrical vehicles (EVs) and reduce the weight of the energy storage devices, wireless charging technology has been widely studied, updated, and commercialized in recent decades, regarding to its distinct superiority of great convenience and low risk. A higher coupling coefficient is the key factor that impacts the transmission efficiency, thus in most medium-power (hundreds of watts) to high-power (several kilowatts) wireless charging systems, ferrites are used to guide the magnetic flux and intensify the magnetic density. However, the weight of the ferrite itself puts an extra burden on the system, and the core loss during operation also reduces the total efficiency and output power. This paper proposes an optimized design algorithm based on a core-less method for the magnetic core, where the core loss and the coupling coefficient are consequently balanced, and the overall weight and efficiency of the system can be optimized. The iteration procedure is applied on the basis of removed ferrite length and thickness in the algorithm. In the simulation, a square coupler with a total volume of 300 mm × 150 mm, a circular coupler of 150 mm × 150 mm and a Double-D (DD) coupler of 300 mm × 150 mm are used to verify the advantages of the proposed method. The optimized ferrite structures are specific for each coupler shape, and the improvement is proved to be universal in current scale by means of 3-D finite element analysis.